Peritonitis in Patients with Scrub Typhus - Lee, Chang-Hun (The American Society of Tropical Medicine and Hygiene, 2012)
Various complications have been reported in scrub typhus cases including acute respiratory distress syndrome, encephalitis, pneumonia, pericarditis, acute renal failure, and acute hepatic failure. Few studies have reported on the gastrointestinal manifestations of scrub typhus. Typical gastrointestinal manifestations in patients with scrub typhus include abdominal pain, nausea, vomiting, hematemesis, melena, and diarrhea. The two cases presented in this study are the first reported cases of peritonitis associated with scrub typhus. This study shows that scrub typhus should also be included in the differential diagnosis of peritonitis in areas where Orientia tsutsugamushi is endemic.